Emotional regulation and physical recovery in young athletes of individual and collective sport modalities. [Regulación emocional y recuperación física de los jóvenes deportistas en modalidades deportivas individual y colectiva]. - Victor Michael Molina; Xavier Oriol; Michelle Celinda Mendoza (Ramón Cantó Alcaraz, 2018)
Due to the influence of positive and negative affects experienced during competition on sports performance, emotional regulation is one of the psychological variables that are more interesting to the sport psychology field. In this sense, this study analyzes how the use of reappraisal and suppression stimulates or hampers the physical recovery of young athletes. All of this taking into account the mediating role of self-efficacy and cognitive anxiety experienced during competition. Three hundred Chilean athletes with ages from 11 to 18 years old participated in this study (M = 15.15; SD = 2.38). Specifically, 139 of them practiced individual sports (boating, athletics, swimming, rhythmic gymnastics and tennis) and 161 collective sports (basketball, volleyball, soccer and rugby). Results show that the use of cognitive reappraisal as a dispositional strategy is associated with positive affect. In addition, cognitive reappraisal promotes self-efficacy in athletes during competition and stimulates their physical recovery. Emotional suppression produces the opposite effect, being associated to negative affect and impairing physical recovery by cognitive anxiety. Results are also discussed related to differences observed in the use of these two emotional regulation strategies in individual and collective sports, along with their practice implications for the training of young athletes in both modalities. Resumen La influencia que los estados emocionales tienen en los deportistas cuando compiten ha hecho que la regulación emocional sea una de las variables psicológicas más interesantes a estudiar en los últimos años en el ámbito deportivo. En este sentido, este estudio analiza cómo los usos de las dos estrategias de regulación más usadas de forma disposicional favorecen o disminuyen la recuperación física de los deportistas jóvenes después de la competición. Todo ello teniendo en cuenta el papel mediador que la autoeficacia y la ansiedad cognitiva tienen en esa relación. Para este estudio se contó con la participación de 300 deportistas chilenos de 11 a 18 años (M = 15,15; DT = 2,38). En concreto, 139 practicaban deportes individuales (canotaje, atletismo, natación, gimnasia rítmica y tenis) y 161 deportes colectivos (básquetbol, voleibol, fútbol y rugby). Los resultados del estudio muestran que el uso de la reevaluación cognitiva como estrategia disposicional favorece la autoeficacia de los deportistas en competición y mejora la recuperación física. La supresión emocional, en cambio, se muestra como una estrategia desadaptativa que favorece la ansiedad cognitiva en competición y dificulta la recuperación física. Se discuten también los resultados respecto a las diferencias observadas en el uso de estas dos estrategias de regulación en deportes individuales y colectivos, y su implicación práctica en la preparación de los deportistas jóvenes en ambas modalidades deportivas.